2017
DOI: 10.1016/j.actamat.2016.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intrinsic kink-like defects on screw dislocation – coherent twin boundary interactions in copper

Abstract: The interaction mechanisms between a dislocation and a twin boundary in nanotwinned face-centered cubic metals are well understood in terms of perfect coherent interfaces. Processes involving intrinsic incoherent twin boundary defects, however, remain largely unexplored, despite recent evidence suggesting that imperfect twin boundaries containing short kink-like step defects contribute notably to plastic deformation and twin stability in large nanotwinned grains. Here, molecular dynamics simulation is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The pattern of twin boundary migration and transmission across twin boundary event in our simulation is also investigated in some experiments [19,34,43]. Fang et al [17] found that in tensile simulation, a single kinked defective twin boundary could change the mechanisms from direct dislocation transmission to dislocation absorption, which is in good agreement with our simulation result. So it is reasonable to explain that the delay effect of the dislocation transmission is caused by the interaction between the dislocation and kink-like defect.…”
Section: Dislocation Transmissionsupporting
confidence: 87%
See 1 more Smart Citation
“…The pattern of twin boundary migration and transmission across twin boundary event in our simulation is also investigated in some experiments [19,34,43]. Fang et al [17] found that in tensile simulation, a single kinked defective twin boundary could change the mechanisms from direct dislocation transmission to dislocation absorption, which is in good agreement with our simulation result. So it is reasonable to explain that the delay effect of the dislocation transmission is caused by the interaction between the dislocation and kink-like defect.…”
Section: Dislocation Transmissionsupporting
confidence: 87%
“…Recently, only few researchers have studied the effects of these kink defects on the deformation mechanism. Fang et al [17] learned that the kink defect in the twin boundary could change the interaction between dislocation and twin boundary from dislocation transmission to dislocation absorption. Xing et al [18] performed the uniaxial tension on copper nanowire with kink-like defective twin boundaries and the kink density substantially affect the yielding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Following the methodology in the literature [74], Figure 4 direction. Kink steps can be viewed as one small segment of an incoherent Σ3 (112) twin boundary, containing three pure partial dislocations, as described in past atomistic studies [82]. Again, our new potential, as well as six other potentials, predicts the same structure in this kink despite the fact that it was not included in the potential fitting procedure.…”
Section: Semi-empirical Potential Developmentmentioning
confidence: 60%
“…Past theoretical studies have shown a correlation between the equilibrium structure of the Σ9 symmetric tilt GBs and the metal type: fcc metals with low stacking fault energy such as Cu tend to favor pure E structural units, whereas those with high stacking fault energy such as Al, favor CB structural units[79].Figure 5(a)shows the equilibrium structure of a Σ9 (221) symmetric <110>-tilt GB predicted in pure Ag from ab initio calculations. Consistent to the literature findings[80], only E structural units are present in this type of boundary.Likewise, our new potential, as well as six other potentials, predicts the same E structural units in this interface, although this structure was not directly included in the potential fitting process.Moreover, the kink step defects attached to coherent twin boundaries are found to be pervasive in as-deposited nanotwinned Cu, and have proved to be important for understanding the plastic deformation mechanisms of nanotwinned fcc metals[81,82].…”
mentioning
confidence: 99%
“…Furthermore, the theoretical results also predict that the confined range is strongly related to the orientation angle of the TB with the tensile stress and the types of partial dislocations. For example, the λ is 4.8–186 nm for the 60° system at 85.2°, and 6.7–237 nm for the screw system at 26.5° (see Supplementary Figure 6), where the two orientation angles are thought to easily trigger NTs in the two partial systems 15,16 . Notably, the twinning stress decreases linearly with the increase of λ , suggesting that the NTs with larger λ generate secondary twins more easily.…”
Section: Discussionmentioning
confidence: 99%